Material scope of Regulation 44/2001 and state immunity from jurisdiction: the ECJ Judgement in the Rina case - Fossati, Curzio (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This paper deals with the recent judgment of the ECJ in the Rina case, concerning the liability of classification and certification bodies of a flag ship, for the damages caused by the sink of that ship, and the question whatever these kind of disputes concerns «civil and commercial matters» and fall within the scope of Regulation 44/2001. The ECJ’s decision also addresses the question whether the defendant companies benefit from State immunity from jurisdiction, recognized by customary international law to the State by delegation of which they carried out the aforementioned operations. The paper tackles, in particular, the relationship between material scope of Brussels I Regulation and State immunity, as well as the impact of immunity on European Union law. Finally, the paper focuses on thebalance between right to effective judicial protection and State immunity, which risk entering into conflict in the present case.
Keywords: Regulation No 44/2001/EC (and No 1215/2012/EU); civil and commercial matters; immunity from jurisdiction of foreign States; ship classification and certification operations; effective judicial protection